(untitled) (International relations and international law Journal, 2018)
This article deals with the impact of the resource wealth of the nature of the country’s economic development. Interrelations “wealth of natural resources” and “economic growth”, as well as their influence on each other is widely known in economic science. According to research by many economists, the presence of rich natural resources for many countries not turns good and inevitable “curse”, which affects the economic progress and development of the country, manifested in the macroeconomic instability and low long-term economic growth. In this paper, the main objective is a clear reflection of the role of natural condition and natural resources in the economy. How territorial features and natural wealth acts as the government instrument in the economic development of the country as a whole? The article presents an overview of approaches of a natural resources assessment and classification of natural resources with the purpose to carry out an economic assessment. At an assessment the main problems comes from lack of the standard methodology of economic assessment of resources and processes of a resources consumption and weakness of the corresponding legal, normative-methodical base. It doesn’t allow to consider and reflect natural resources in structure of national wealth of the country together with the cost of the fixed production assets, buildings and constructions. In this regard, the main task consists in development of the general concept of an economic assessment of natural resources which would allow to develop uniform system of indicators for an assessment of a various nature forming components, which is optimal from sight of coordination of environmental management and economy interests. Nowadays in economic science the main approaches of an economic assessment of natural resources are developing for their reflection in structure of national wealth. Key words: natural resource, abundance of natural resources, resource wealth, “resource-abundant” countries, capital, income, raw.